Recommendations for structural assessment of RC slabs using the finite element method - Plos, Mario; Johansson, Morgan; Zandi, Kamyab; Shu, Jiangpeng (Bridge Maintenance, Safety, Management, Digitalization and Sustainability, 2024)
To mitigate environmental impact and societal costs, there is a need to extend the lifetime of existing transportation infrastructure. Research has shown that many structures, such as bridges, have a substantial inherent load-carrying capacity that is often not fully utilized. In the research presented, it was shown how non-linear numerical analysis can be used to show higher performance and longer lifetime than with conventional engineering methods. Comprehensive recommendations for use in engineering practice have been developed for the structural assessment of reinforced concrete slabs using the finite element method. A multi-level structural assessment strategy was developed to provide a framework for successively improved and more advanced analysis. For the more advanced levels, non-linear FE analysis is used, adopting a global safety format and incorporating the effects of deterioration. With such analyses, the structural behaviour can be more accurately described and higher, yet conservative load-carrying capacities can generally be demonstrated.